1977
DOI: 10.1111/j.1399-6576.1977.tb01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Passage of Ketamine after Intravenous Administration

Abstract: This study was designed to measure how fast and at what concentrations ketamine would enter the foeto-placental circulation, when administered intravenously to 10 healthy mothers immediately before forceps delivery, which was indicated by a delayed second stage of labour. It is shown that ketamine very rapidly passes the placenta, and that ketamine levels in cord blood exceed the levels in the maternal venous blood as early as 1 min 37 s after the injection. The ketamine levels in cord blood reach a maximum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 6 publications
1
13
0
2
Order By: Relevance
“…respiratory depression. [60] 3.1.5 Opioids usually administered after delivery of the fetus to maintain muscle Occasionally, high doses of opioids are used to induce general relaxation after the effects of suxamethonium chloride wear off. In anesthesia.…”
Section: Ketaminementioning
confidence: 99%
“…respiratory depression. [60] 3.1.5 Opioids usually administered after delivery of the fetus to maintain muscle Occasionally, high doses of opioids are used to induce general relaxation after the effects of suxamethonium chloride wear off. In anesthesia.…”
Section: Ketaminementioning
confidence: 99%
“…Fetal blood levels have been reported to be comparable to maternal blood levels within 2 min of maternal administration. 61 Ketamine is distributed rapidly after IV administration and plasma levels decrease rapidly thereafter. 62,63 In our recent publication, 35 we reported that the ketamine levels required to maintain anesthesia were 10 to 25 g/mL, which is 5 to 10 times higher than those observed in humans (2-3 g/mL).…”
Section: Ketamine-induced Neuronal Cell Death In the Perinatal Rhesusmentioning
confidence: 99%
“…Ketamine rapidly crosses the placenta, and the plasma concentration in mixed cord blood is similar to the maternal venous level, 1.5 to 6.5 minutes after maternal administration (Ellingson et al, 1977). Neonatal depression has been associated with the use of ketamine as an anaesthetic agent at the time of delivery (Little et al, 1972;Ellingson et al, !…”
Section: Ketaminementioning
confidence: 99%